Shaftesbury on the Beauty of Nature - Michael B. Gill (Journal of Modern Philosophy)
Many people today glorify wild nature. This attitude is diametrically opposed to the denigration of wild nature that was common in the seventeenth century.One of the most significant initiators of the modern revaluation of nature was Anthony Ashley Cooper, the third Earl of Shaftesbury (1671–1713). I elucidate here Shaftesbury’s pivotal view of nature. I show how that view emerged as Shaftesbury’s solution to a problem he took to be of the deepest philosophical and personal importance: the problem of how worship of God can be both transportingly emotional and entirely rational.In section 1 I sketch the denigration of wild nature in two of Shaftesbury’s predecessors: Burnet and Locke. I next turn to Shaftesbury’s problem, describing in section 2 the love of God he aspired to and in section 3 his commitment to rational religion. I then explain Shaftesbury’s solution, describing in section 4 his view of beauty in general and in section 5 his view of the beauty of nature.